З історії Херсонеса Таврійського другої половини IV — початку III ст. до н. е. - Зубар, В.М. (Археологія, 1990)
У статті простежується процес переростання Херсонського полісу в центр порівняно великого державного утворення, до складу якого наприкінці IV— початку III ст. до н. е. були включені землі Північно-Західного Криму, населеного різними соціальними верствами населення. В статье на конкретном историко-археологическом материале анализируется процесс перерастания автономного Херсонесского полиса в центр сравнительно обширного территориального государственного образования, в состав которого в конце IV — начале III вв. н. э. были включены греческие поселения и укрепления Северо-Западного Крыма. Земли в этом районе в результате целенаправленной политики перешли под юрисдикцию Херсонеса, а его население за пользование ими должно было платить форос. Таким образом, Херсонесская гражданская община получала из Северо-Западного Крыма ренту-налог, которая, с одной стороны, являлась средством эксплуатации населения этого района, а с другой — одним из главных условий расцвета Херсонеса. Автор приходит к выводу о том, что процессы, прослеживающиеся в социально-экономическом и политическом развитии Херсонеса в рассматриваемый период, позволяют говорить о начале качественно нового этапа в истории города, который по общепринятой терминологии может быть назван эллинистическим. Необходимость правового закрепления экономических и социально-политических основ Херсонесского государства в конечном итоге и привели к изданию присяги, которую принимали все полноправные граждане нового государства. Using the concrete historico-archaeological data as a basis, the author analyzes the process of the Khersones policy transformation into a comparatively vast territorial statehood that embraced Greek settlements and fortifications of the North-Western Crimea in the late 4th and early 3d cent. B.C. As a result of the purposeful policy lands in this region were given under the jurisdiction of Khersones and population of this region was obliged to pay a phoros for using the lands. So, the Khersones civil community obtained a dutyrent from the North-Western Crimea. On the one hand it was a means of the population exploitation, on the other — it served as one of main conditions favouring the Khersones flourishing. The author comes to the conclusion that processes observed in the socio- eeconomic and political development of Khersones in the period under study permit considering them as a beginning of the qualitatively new stage in the history of the town. That stage in the line with the generally used terms may be called an Hellenistic one. At that time the process of transformation of the classic autonomous policy into a vast territorial state amalgamation had been finally completed in Khersones. The necessity of legal consolidation of economic and socio-political bases of the Khersones state has resulted in publication of the oath which was taken by each full and equal citizen of the new state.